The Selection of Bacterial Strain and Inoculum Concentration in Microbial Bioassay for the Development of Cefixime Potency Test in Pharmaceutical Preparations - Islamie, Ridho; Raharjo, Dian Natasya; Agustiningrum, Nur (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Cefixime is one the antibiotic that use widely in the clinical setting. Microbiological bioassay is an essential step to ensure the efficacy of the antibiotic. Several factors including bacterial strain, inoculum concentration, and solvent, pH, reference concentration, storage time of antibiotic standard influenced the zone inhibition of the bioassay. This study was aimed to optimize two factors from microorganism aspect for the development antibiotic potency test of cefixime in pharmaceutical preparation. Cylinder cup method was used for this microbiological assay. Our results revealed that Escherichia coli ATCC 10536 with the concentration of 1.0% was the optimum bacterial strains for cefixime reference standard. In conclusion, the optimizing both factors from the test microorganism could be helpful to develop the appropriate method for microbial bioassay of Cefixime in pharmaceutical preparations.